Measles Disease Model using Censored Hurdle Negative Binomial Regression in East Java - Aida, Liza Nur; Layla Nur Karisma, Ria Dhea (Proceedings of the International Conference on Green Technology; Vol 11 No 1 (2021): Proceeding of International Conference on Green Technology, 2021)
Abstract- Measles is an infectious disease caused by measles virus and contagious. In recent years, especially in Indonesia, the number of measles rates have decreased at 2021 then some observations were worth zero. Hurdle Negative Binomial Regression is a method that used to overcome excess zero and over dispersion. Furthermore, count data is a data with non-negative integers that showed the number of event then it unable to use Poisson Regression. The aim of the study is to obtain measles model using HNBR in Eat Java. Based on the result of study, the factors that influence are vitamin A distribution, malnutrition in toddlers, and population density in East Java.